Thrombus formation and structure and the evolution of mass effect in intracranial aneurysms treated by balloon embolization: emphasis on MR findings. - Strother, C M; Eldevik, P; Kikuchi, Y; Graves, V; Partington, C; Merlis, A (American Journal of Neuroradiology, 1989)
This study was designed to further assess the capabilities of MR as a tool for the diagnostic evaluation of patients with giant intracranial aneurysms, to determine MR's ability to define the degree of thrombosis present within giant aneurysms before and after treatment with balloon occlusion, and to delineate the MR characteristics of both spontaneous and induced thrombus within giant aneurysms. Nine patients with unclippable intracranial aneurysms treated by parent artery occlusion with detachable balloons were evaluated with MR, angiography, and CT. Pretreatment and posttreatment MR studies were evaluated for their ability to (1) define the size, configuration, and anatomic relationships of an aneurysm; (2) detect and characterize thrombus within an aneurysm; and (3) determine if treatment successfully caused complete aneurysm thrombosis. MR imaging does not replace angiography in either the pretreatment or the posttreatment evaluation of patients with giant intracranial aneurysms. Thrombus formation and dissolution is a complex, dynamic process. Active thrombus in incompletely thrombosed aneurysms differs from isolated organizing thrombus in completely thrombosed aneurysms. Induced and spontaneous thrombi differ in mechanisms of formation and in composition; their MR characteristics are also different. Reduction in mass effect is common after complete thrombosis of giant intracranial aneurysms.